Left radicalism in India - Chakrabarty, Bidyut (New York Routledge, 2015)
"Left radicalism in India was rooted in the nationalist movement and was set in motion in the 1920s with the formation of the communist party. The communist movement manifested itself differently in each phase of India's political history and Communism continues to remain a meaningful alternative ideological discourse in India. This book examines left politics in India focusing on its rise, consolidation and relative decline in the present century. Left radicalism in India is a distinct ideological phenomenon which is articulated in two complementary ways: while the parliamentary left remains social democratic in character, its bête noire, the left wing extremists, continue to uphold the classical Marxist, Leninist and Maoist notion of violent revolution. By concentrating on the nature and also activities of these two versions of left radicalism, this book is a thorough study of the phenomenon. The author analyses the states of Kerala, West Bengal and Tripura and presents a variety of case studies of communist movements. He argues that the political power of the left parties depends on the degree to which they have built organizational strength, political hegemony and a broad social base through legal and extra-parliamentary struggles. An in-depth study of socio-economic circumstances that remain critical in conceptualizing radical extremism, Left Radicalism in India will be of interest to those studying Indian Politics, South Asian History, Development Studies and Global Politics"--
Keywords: Communism -- Consolidation of left radicalism in India -- Socio-economic contexts of left radicalism in India -- Constituents of left radicalism in India -- Parliamentary left in India: Articulating social democracy as a universal theoretical design -- Parliamentary left in Tripura: social democracy in a new mould -- Parliamentary left in West Bengal : Rise and fall of a hegemonic regime -- Parliamentary left in Kerala: redesigning parliamentary democracy amidst ideological elasticity -- Left-wing extremism in India: an Indigenous endeavour at ideological innovations -- Historical roots and gradual consolidation of the moaist -- Left wing radicalism in practice in Orissa: field based analysis; Communist parties; HISTORY / Asia / India & South Asia; POLITICAL SCIENCE / General